Gender differences in the pre-competition temporal pattering of anxiety and hormonal responses - Thatcher, J.; Thatcher, R.; Dorling, D. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: This study examined gender differences in the pre-competition temporal patterning of anxiety and hormonal responses. METHODS: Six male and 6 female field hockey players completed the modified Competitive State Anxiety Inventory-2, including both intensity and direction subscales, and provided saliva and urine samples 24, 2, and 1 hour prior to competition. These samples were analyzed for cortisol, and noradrenaline and adrenaline, respectively. RESULTS: Two x 3 repeated measures ANOVAs revealed significant gender x time interactions for cognitive and somatic anxiety intensity and adrenaline and noradrenaline, but not cortisol. While males' anxiety and hormonal responses demonstrated no significant changes, significant increases in females' anxiety, and significant decreases in their adrenaline and noradrenaline were observed over time. Moreover, while males' anxiety and hormonal responses mirrored each other, this was not the case for the females with increases in females' cognitive and somatic anxiety intensity levels accompanied by decreases in adrenaline and noradrenaline. CONCLUSIONS: Although this study has extended this line of research by adopting a psycho-physiological approach and measuring anxiety intensity and direction in male and female athletes, replication is required with larger samples from a greater diversity of sports.